Structure and decomposition of diol inclusion compounds - Su, Hong (Department of Chemistry, 2018)
The inclusion properties of the host, trans-9, 10-dihydroxy-9, 10-diphenyl-9,10- dihydroanthracene, with various guest molecules, namely cyclohexanone, 2- methylcyclohexanone, 3-methylcyclohexanone and 4-methylcyclohexanone, were investigated. The host to guest ratios were determined by programmed temperature thermogravimetry. Two of the four molecular structures were elucidated using single crystal X-ray diffraction. All the inclusion compounds were also characterised by differential scanning calorimetry, hotstage microscopy and Xray powder diffraction. The kinetics of decomposition of the inclusion compound containing the guest cyclohexanone were studied using different experimental techniques under isothermal conditions: these were the quartz microbalance, the levitating balance and isothermal thermogravimetry. The kinetics of decomposition of the other three compounds were studied by means of isothermal thermogravimetry. The Arrhenius parameters determined showed a compensation effect between the activation energies and pre-exponential factors. Competition experiments were performed to determine the selectivity of the host for the four guest substances.